(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
As a matter of fact, the existence of the oil fields and the work of the oil companies in the residential areas have an impact on the style and standard of living of the local communities and the consequential change in society. The problem, in this research, represents the big rise in the illiteracy rate, the falling level of education and the high unemployment rate in the local communities that are found in Al Gharraf oil field. The most important objectives of the research is to identify the main methods and procedures carried out by Petronas which help the local communities in Al Garraf oil field so as to ensure the development of their skills through learning and building of their own abilities through the establishment of Al Gharraf vocational training center. The study adopts the analytical descriptive approach by identifying the problem and find out the impact of Petronas which is subjected to the analysis by the interview and the questionnaire form .They were distributed in the study area.The most important results that have been reached that the presence of Petronas and the establishment of Al Gharraf vocational training center haveÂ a positive impact on the development of people skills to ensure that they are qualified for work in Petronas Company or its members or the rehabilitation and education of individuals toward getting a certain craft and helping to start a particular work.